Toleransi UmaT Beragama di desa loloan, JemBrana, Bali (ditinjau dari Perspektif sejarah) - KARIM, M. ABDUL (Analisis: Jurnal Studi Keislaman, 2016)
This paper aims to discuss the history of religious tolerance in Jembrana, Bali, which is shaped by the culture embraced by the local community; both Hindus and Muslims. Culture itself can be a unifier of the differences that exist, including in terms of religious differences. Based on that, the reality of Jembrana society, which repersent Balinese culture with religious diversity (Hinduism as a native and Islam as migrants from Java and Makassar) could be approached through a cultural one. This study traces the historical record of religious harmony in Jembrana, ranging from the advent of Islam, the local responses to it, and the harmonious relations between Muslims and Hindus in the light of cultural frame.